2012
DOI: 10.1088/0022-3727/45/39/395401
|View full text |Cite
|
Sign up to set email alerts
|

Si surface passivation by SiOx : H films deposited by a low-frequency ICP for solar cell applications

Abstract: Hydrogenated silicon suboxide (SiO x  : H) thin films are fabricated by a low-frequency inductively coupled plasma of hydrogen-diluted SiH4 + CO2 at a low temperature (100 °C). Introduction of a small amount of oxygen into the film results in a predominantly amorphous structure, wider optical bandgap, increased H content, lower conductivity and higher activation energy. The minority carrier lifetime in the SiO x  : H-passivated p-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In order to further investigate the influence of CO 2 partial pressure on the film property, FTIR analysis was carried out. The results are shown in bonding group is not observable, which is similar to other a-SiO :H(i) thin films commonly reported in the literature [15,19,37]. The Si-C or C-H bonding configuration is also not clearly visible in the spectra due to extremely small inclusion of C atoms in the film [50,51].…”
Section: Bonding Configuration Analysissupporting
confidence: 77%
See 2 more Smart Citations
“…In order to further investigate the influence of CO 2 partial pressure on the film property, FTIR analysis was carried out. The results are shown in bonding group is not observable, which is similar to other a-SiO :H(i) thin films commonly reported in the literature [15,19,37]. The Si-C or C-H bonding configuration is also not clearly visible in the spectra due to extremely small inclusion of C atoms in the film [50,51].…”
Section: Bonding Configuration Analysissupporting
confidence: 77%
“…It is interesting to observe that the Si-O-Si stretching peak at 1107 cm −1 becomes more significant with higher compared to that at 1053 cm −1 . Jana et al [37] and Zhou et al [15] associate these peaks to Si-H(Si 3− O ) with = 2 and 1, respectively, according to random bonding model [53]. The increase of peak intensity at 1107 cm −1 indicates an increase of Si-H(SiO 2 ) bonding concentration.…”
Section: Bonding Configuration Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the onset of H effusion, effects of these two phenomena cannot be distinguished in this case. Compared with Zhou et al [40], who showed a crystalline interfacial layer of about 30 nm, the suppression of such layer formation by using the optimal deposition conditions in this paper is the key to achieving high passivation quality and an improved process window.…”
Section: Interfacial Structurementioning
confidence: 79%
“…To overcome bulk lifetime degradation, a low-temperature SiO x deposition by PECVD has been studied by different groups [33][34][35] for surface passivation. Another option for the synthesis of SiO x is a chemical oxidation of the Si surface using nitric acid (HNO 3 ).…”
Section: Sio Xmentioning
confidence: 99%